Inhibitory effect of mesenchymal stem cells on lymphocyte proliferation. - Gao, K.; Chen, Younan; Wei, L.; Li, S.; Jin, X.; Cong, C.; Yuan, Y.; Long, D.; Li, Y.; Cheng, J.; Lu, Y. (2008)
We investigated the mechanism underlying the inhibitory effect of rat mesenchymal stem cells (MSCs) on non-specific mitogen-stimulated lymphocytes (LCs) and lymphoblasts (LBs). We used MSCs of passages 2-8 prepared from Sprague-Dawley (SD) rats. LCs were isolated from the spleens of SD rats. Mixed LCs reactions of mitomycin C-treated MSCs with concanavalin A (ConA)-stimulated LCs or LBs were performed, and the proliferation inhibition effect was tested by MTS assay. The cytotoxicity of MSCs against naïve and ConA-stimulated LBs was detected, after co-culturing for 24 h, by lactate dehydrogenase release assay. The rate of apoptosis of ConA-stimulated LBs was measured by flow cytometry after incubation with MSCs for 9 h in the ratio 10:1. The MSCs were treated with Fas ligand (FasL), transforming growth factor (TGF)-beta, and interleukin (IL)-10 blocking antibodies and co-cultured with ConA-stimulated LBs to observe the apoptosis and growth inhibitory effect. The main outcomes were bone marrow-derived adherent CD29+, CD44+, CD45-, CD54+, CD95+, and SH-2+ MSCs. FasL, TGF-beta, and IL-10 production by MSCs were visualized by immunocytochemical analysis. MSCs exhibited a dose-dependent growth inhibitory effect on ConA-stimulated LCs and LBs. When treated with anti-FasL and anti-IL-10 blocking antibodies, the inhibitory effect of MSCs on LBs proliferation, and the effect of apoptosis induction on LBs decreased. Anti-TGF-beta blocking antibody treatment did not significantly influence MSCs. Therefore, the inhibitory effects of MSCs against activated LBs were significantly stronger than that against naïve LCs. FasL and IL-10, rather than TGF-beta, play important roles in the immunosuppressive effects of MSCs.